The Relationship Between Self-Efficacy And Academic Stress In High School Students - Wilda Deliana Harahap; Firman; Mohd Nazri Abdul Rahman; Netrawati (Journal Of Psychology, Counseling And Education, 2024)
This research aims to investigate the role of education in students' lives and development, as well as the impact of academic stress on their mental well-being and learning outcomes. The research approach used is a literature study, which involves searching and analysing literature from various sources such as books, journals and related research. The results showed that university students often face academic stress. This research reveals the importance of self-efficacy or self-belief in coping with academic stress. The results showed that individuals with high levels of self-efficacy are more likely to be able to manage academic stress and remain motivated in achieving academic goals. The existence of a positive relationship between self-efficacy and academic stress levels highlights the importance of developing self-efficacy as a key strategy in dealing with academic stress. This research also highlights the need for appropriate support and strategies to help students manage academic stress, with the aim of improving the learning process and reducing its negative impact.